The impact of human resource practices on perceived employee performance at HeiTech Padu Berhad / Nur Izzati Shamsuddin and Raja Nur Sakinah Raja Zainal Alam Shah - Shamsuddin, Nur Izzati; Raja Zainal Alam Shah, Raja Nur Sakinah (Faculty of Business and Management, 2016)
This paper was aimed to study the impact of human resource practices on perceived employee performance at HeiTech Padu Bhd. The independent variables of the study are recruitment and selection practices, compensation practices, and employee performance evaluation practices whereas the dependent variable is perceived employee performance. Data was collected by using questionnaires and it was distributed to the employees of HeiTech Padu Bhd whose placed at the headquarters in Subang Jaya. Data obtained was then analysed using IBM SPSS Statistics 20.0. The results revealed that there is a positive relationship between human resource practices and perceived employee performance. It was also found that recruitment and selection practice is the most significant factor that affects perceived employee performance.